Influencia de la violencia familiar en el aprendizaje de los niños/as de educación inicial - Oliveira Ruiz, Jassy (2008)
Today, the issue of violence left space private and secret from the public space and is currently one of the serious social problems that crosses the different primary and secondary networks of society, places pluriprofesional intervention. Extortion, insults, threats, shouts, slapping, beating, spanking, the dark room, the cold shower, the obligatory fast, mandatory food, prohibiting leave, prohibition of saying what you think the prohibition of doing what feels and public humiliation are some of the traditional methods of penitence and torture. For punishment of disobedience and punishment of freedom, family tradition perpetuates a culture of terror that humiliates, teaches children to lie and spread the plague of fear and culture of terror. Violence within the family is not a recent phenomenon, however, has been a feature of family life accepted since ancient times. However not begin to become aware as very serious social phenomenon until the sixties in Anglo-Saxon countries and in the eighties in our country. Feminist movements are the starting claims for women's rights. Social perception and recognition that certain behaviors are violent, it is historical. That perception is determined by power relations and the values ​​in a given society at specific historical moments. We live in societies that handle different codes in relation to violence; there is a strong condemnation when it takes place in public space, however it tolerates and supports when given in the private space. A complaint of an assault on public roads is immediately welcome, the same complaint is dismissed home, undervalued and even try to persuade the victim to withdraw its complaint. The childhood abuse, domestic violence, sexual assault and other forms of violence, are directly connected with the place that women occupy in society. The social representation on violence in the family environment is changing; however, there are many families who continue to assume that the use of violence within the family is natural and often positive, especially with regards to child abuse. Paradoxically what is silenced, that which remains hidden socially not mean it is a hard fact to perceive. In the case of domestic violence the phenomenon is not because it has made us everyday, has been "naturalized" it has become an expected situation in a given context. The social representation on violence in the family environment is changing, however, there are many families who continue to assume that the use of violence within the family is natural and often positive, especially in regard to abuse childish. However, where the problem of family violence is crucial and patentiza clearly, it is at school. The boy and the girl feel particularly helpless and vulnerable. They may be afraid and develop a few strategies to address conflict situations. Many (as) tend to violate the rules aggressively